2016
DOI: 10.3390/ijms17040589
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Pharmacological Profiles of Three Fagopyrum Buckwheats

Abstract: The genus Fagopyrum (Polygonaceae), currently comprising 15 species of plants, includes three important buckwheat species: Fagopyrum esculentum (F. esculentum) Moench. (common buckwheat), Fagopyrum tataricum (F. tataricum) (L.) Gaertn. (tartary buckwheat) and Fagopyrum dibotrys (F. dibotrys) (D. Don) Hara. (perennial buckwheat), which have been well explored due to their long tradition of both edible and medicinal use. This review aimed to present an up-to-date and comprehensive analysis of the phytochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 60 publications
1
74
0
2
Order By: Relevance
“…The working method, in terms of the vegetal biological material Fagopyrum esculentum Moench., has involved the compliance with the work conditions at the hood and it consisted of the following: seeds aseptization, by means of ethylic alcohol solution (C 6 The incubation conditions provided for the temperature of 21°C ± 2°C, as well as for the enforcement of treatments for 16 hours within 24 h period of time (Lin et al, 2013). Treatments have been applied after the first 72 h. During the first 72 h, seeds have been kept in the dark.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The working method, in terms of the vegetal biological material Fagopyrum esculentum Moench., has involved the compliance with the work conditions at the hood and it consisted of the following: seeds aseptization, by means of ethylic alcohol solution (C 6 The incubation conditions provided for the temperature of 21°C ± 2°C, as well as for the enforcement of treatments for 16 hours within 24 h period of time (Lin et al, 2013). Treatments have been applied after the first 72 h. During the first 72 h, seeds have been kept in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…(buckwheat), of Polygonaceae family and Fagopyrum type (Jing et al, 2016), is a species of an annual herbaceous plant, originating from Tibet, having multiple uses in human food, zootechnical industry, apiculture and human medicine (Pârvu, 1997). This is a species with valuable composition seeds (proteins, food fibers, lipids with unsaturated fats, vitamins, amino acids, antioxidants, phenols, flavonoids -Pârvu, 1997; Alvarez-Jubete et al, 2010; Jing et al, 2016;Park, 2017), for human nutrition. Fagopyrum esculentum Moench.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of bioactive phenolics including flavonoids, condensed tannins, and phenylpropanoids and phenol derivatives were isolated from those buckwheat species. Flavonoids in Fagopyrum buckwheats exhibited remarkable antioxidant and cardio-cerebral vascular protective effects hence they were considered important dietary supplements 6 . It has been reported that buckwheat seed powder solution shows non Newtonian flow and it can be used as biodegradable polymer in various dosage forms 7 .…”
Section: Ijpsr (2018) Volume 9 Issue 4 (Research Article)mentioning
confidence: 99%
“…Four catechins and rutin were isolated from ethanol extracts of Fagopyrum esculentum groats. The structures of these catechins were established as (−)-epicatechin, (+)-catechin 7-O-β-D-glucopyranoside, (−)-epicatechin 3-O-p-hydroxybenzoate, and (−)-epicatechin 3-O-(3,4-di-O-methyl) gallate [63].Chemical analysis showed that the plant also contained, cyclitol: (fagopyritol A1, fagopyritol A2, fagopyritol A3, fagopyritol B1, fagopyritol B2 and fagopyritol B3); triterpenoids: (olean-12-en-3-ol and urs-12-en-3-ol); steroids: (6-hydroxystigmasta-4,22-dien-3-one, S-methylcholesterol, stigmast-5-en-3-ol, stigmast-5,24-dien-3-ol and trans-stigmast-5,22-dien-3-ol); fatty Acids: (6, 7-dihydroxy-3,7-dimethyl-octa-2(Z),4(E)-dienoic acid, 6, 7-dihydroxy-3,7-dimethyl-octa-2(E),4(E)-dienoic acid and 4, 7-dihydroxy-3,7-dimethyl-octa-2(E), 5(E)-dienoic acid); γ-tocopherol and squalene [64][65][66][67].Buckwheat has a strong characteristic aroma. Volatiles from a freshly ground buckwheat flour were extracted by different methods The compounds with the highest contribution to the buckwheat aroma were: 2,5-dimethyl-4-hydroxy-3(2 H )-furanone, (E, E)-2,4-decadienal, phenylacetaldehyde, 2-methoxy-4-vinylphenol, ( E )-2-nonenal, decanal, hexanal and salicylaldehyde (2-hydroxybenzaldehyde) [68].…”
Section: Ii-chemical Constituentsmentioning
confidence: 99%